Influence of low-pulsed frequency on arc profile and weld formation characteristics in double-pulsed VPTIG welding of aluminium alloys - Wang, Yipeng; Cong, Baoqiang; Qi, Bojin; Chen, Xin; Yin, Yuhuan; Lin, Sanbao (Elsevier, 2020)
AA2219 aluminium alloy plates were processed by double pulsed variable polarity tungsten inert gas (DP-VPTIG) welding, and the influence of low-pulsed frequency on arc profile, weld appearance and penetration characteristics were investigated. An image processing algorithm was proposed for arc edge extraction and arc feature sizes acquisition. The arc energy equations in low-frequency pulse peak stage (tp) and base stage (tb) were established based on the electrical parameters. The arc profile periodically expanded in tp and shrunk in tb, resulted from the difference in arc energy of the two stages. The pulsation effects in arc profile, weld appearance and penetration, caused by the pulsed arc were observed to exhibit a decreasing trend with the increase of low-pulsed frequency (fL). The pulsation effects were obvious when fL was 0.5 Hz, then became weak and tended to disappear as fL increased above 3 Hz. The empirical correlations between fL and the pulsation effects of arc profile, weld appearance and penetration were respectively developed. It is recommended to use fL in the range of 1–2 Hz to properly exert the low-frequency pulsation effect. The results provide a valuable basis for controlling and optimizing the DP-VPTIG process in the high efficiency welding of aluminum alloys
Keywords: Aluminium alloy; Tungsten inert gas welding; Weld formation; Double pulses; Welding arc